Peripheral isolation and demographic stability are reflected in the genetic diversity of the populations of the Helmeted Manakin: a bird endemic to the gallery forests - THAINARA O. SOUZA; LEILTON W. LUNA; JULIANA ARARIPE; WEBER A. DE G. E SILVA; PÉRICLES S. DO REGO (Anais da Academia Brasileira de Ciências, 2022)
Abstract The Cerrado encompasses a complex network of hydrographic basins, which is responsible for the formation and maintenance of the riparian and gallery forests. Alterations in the vegetation resulting from the paleoclimatic changes that occurred during the Pleistocene influenced the current distribution of these humid forests. To understand of the evolutionary dynamics of this landscape on the population structure of the associated organisms, we studied the population genetics of the Antilophia galeata (Pipridae), a bird endemic to the gallery forests of the Cerrado. For this, we evaluated the variability of the mitochondrial control region of 71 A. galeata specimens from 18 localities distributed throughout the Cerrado. The results indicated the existence of significant substructure among the populations located in the peripheral areas of the Cerrado, in comparison with the populations found in the central portion, reflecting historical changes in the environment. We also found high levels of diversity in all the populations, while the analysis of the demographic history revealed a scenario of stability. Overall, then, these findings indicate that the historical modifications of the gallery forest distribution may have been most accentuated in the peripheral zones, with a greater stability and connectivity persisting in the central portion of the biome.